Preoperative concomitant chemoradiotherapy in esophageal cancer - Šeruga, Boštjan (Radiology and oncology (Ljubljana), 2006)
Background. Currently primary treatment options for esophageal cancer are surgery only or concomitant chemoradiotherapy (CRT) and the long-term survivalof patients with locally advanced disease is rare. Preoperative concomitant CRT seems to be beneficial, mostly in patients who achieve a complete pathologic response (pCR) after CRT. In this retrospective analysis the efficiency and toxicity of preoperative CRT in patients with locally advanced esophageal cancer was analysed as well as the influence of pCR on thesuraival. Patients and metkods From 1996 to 2002 41 patients with locoregionally confined esophageal cancerwere treated with cisplatin 75 mgžm2 and 5-FU 1000 mgžm2 as 4 day contonuous infusion starting on days 1. and 22. with concorrtitant radiotherapy 4500 cGy, 200-300 cGyžday. Esophagectomy followed 4-5 weeks after radiotherapy. After the surgery patients were followed-up regularly at 3-6 months intervals. Results. The pCR was achieved in 26.8% of patients. The overall median survival time was 18 months for all patients, 21.2 months for patients who achieved pCR and 16 months in those with residual disease (p= 0,79). Postoperative mortality rate was 22%. The median dose intensity for cisplatin was 92% and for 5-FU 71.5 of the planned dose. Disease recurred most often locoregionally (31.7%) and the overall recurrence rate was 43.9. Conclusion. Modern radiation techniques and the adequate dose intensity could further improve the locoregional control. The selection of patients without comorbid conditions and without already present distant metastases is essential for this combined treatment approach.
Keywords: Drug therapy; Esophageal neoplasms; kemoterapija; požiralnik; radioterapija; Radiotherapy; rak (medicina); therapy; zdravljenje